An Analysis of Gender Differences in UK Graduate Migration Behaviour - Alessandra Faggian; Stephen Sheppard; Philip Mccann (European Regional Science Association (ERSA), 2006)
In this paper we employ dichotomous, multinomial and conditional logit models in order to analyse the employment-migration behaviour of some 300,000 UK university graduates. By controlling for a range of variables related to human-capital acquisition and local economic conditions, we are able to distinguish between different types of sequential migration behaviour from domicile to higher education and on to employment. Our findings indicate that UK female graduates are generally more migratory than male graduates. We suggest that the explanation for this result lies in the fact that migration can be used as a partial compensation mechanism for gender bias in the labour market.
Keywords: 330